Which Tendon Plasty Has the Best Outcome? A Comparison of Four Tendon Plasty Techniques in a Large Cohort of Patients with Symptomatic Trapeziometacarpal Osteoarthritis. Issue 2 (8th June 2022) - Hoogendam, Lisa; Bink, Thijs; de Lange, Jurriaan; Selles, Ruud W.; Colaris, Joost W.; Zuidam, J. Michiel; Hovius, Steven E. R.; van der Heijden, Brigitte
Abstract : Background: Trapeziometacarpal osteoarthritis is commonly treated with a trapeziectomy combined with a form of tendon plasty. The type of tendon plasty used is based on the surgeon's preference. The purpose of this observational study was to compare the outcomes of four different tendon plasties combined with trapeziectomy used to treat osteoarthritis of the trapeziometacarpal joint: the Weilby, Burton-Pellegrini, Zancolli, and anchovy plasty procedures. Methods: Patients treated with a trapeziectomy followed by a tendon plasty completed patient-reported outcome measures at baseline and 12 months postoperatively. The primary outcome was the Michigan Hand Outcomes Questionnaire pain subscale. Secondary outcomes were the minimal clinically important difference of Michigan Hand Outcomes Questionnaire pain scale score, Michigan Hand Outcomes Questionnaire hand function, satisfaction, and complication rate. Results: Seven hundred ninety-three patients underwent a trapeziectomy with a tendon plasty between November of 2013 and December of 2018. There was no difference in pain score after 12 months between the four tendon plasty techniques. Patients undergoing an anchovy plasty had a higher chance of reaching the minimal clinically important difference for Michigan Hand Outcomes Questionnaire pain score compared to the other techniques (OR, 2.3; 95 percent CI, 1.2 to 4.6). Overall, more than 80 percent of the patients were satisfied with the treatment outcome, independent of which technique was used. Complication rates of the different techniques were similar. Conclusions: Surgical treatment of osteoarthritis of the trapeziometacarpal joint reduced pain after 12 months, independent of which tendon plasty was used. Patients undergoing an anchovy plasty were more likely to experience a clinically relevant improvement in pain while having similar hand function, satisfaction, and complication rates. This suggests that anchovy plasty is the preferred tendon plasty. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.